THE DEVELOPMENT OF SOCIAL STUDIES TEACHING MATERIALS BASED ON MALAY SIAK SONGKET WEAVING FOR FOURTH GRADE ELEMENTARY SCHOOL STUDENTS - Guslinda; Rita Kurnia; Munjiatun (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Growing awareness of students to love their own culture is not easy, there needsto be an effort to introduce. Culture-oriented learning supported by relevant teaching materials is an articative to the answer. The purpose of this research is the development of IPS elementary teaching material based on Siak Malay songket weaving. It is expected that with the development of teaching materials students will develop a love for their own culture, especially about the weaving of Malay Siak songket and can also increase learning activities. Teaching material products can be used in social studies learning for fourth grade elementary school students, especially on the theme of